Rozwiąż równanie


-(2x+3)= 2 (x-4) + (5x-4)


-3(2x-1) = 4



2t-(3t+1)= 6



3(y+6)-y= 2(y+9)



2(x+1) =x



-(4+x)= 2(3-x)


x -7-2(3x+5)=3


NA TERAZ PLS



Odpowiedź :

- (2x+3) = 2 (x-4) + (5x-4)
- 2x - 3 = 2x - 8 + 5x - 4
- 2x - 2x - 5x = - 8 - 4 + 3
- 9x = - 12 + 3
- 9x = - 9 /: (-9)
x = 1

- 3(2x-1) = 4
- 6x + 3 = 4
- 6x = 4 - 3
- 6x = 1 /: (-6)
x = - 1/6

2t - (3t+1) = 6
2t - 3t - 1 = 6
- 1t = 6 + 1
- t = 7 /: (-1)
t = - 7

3(y+6) - y= 2(y+9)
3y + 18 - y = 2y + 18
4y - 2y = 18 - 18
2y = 0
y = 0

2(x+1) = x
2x + 2 = x
2x - x = - 2
x = - 2

(4+x) = 2(3-x)
4 + x = 6 - 2x
x + 2x = 6 - 4
3x = 2 /: 3
x = 2/3

x - 7 -2(3x+5) = 3
x - 7 - 6x - 10 = 3
x - 6x = 3 + 7 + 10
- 5x = 20 /: (-5)
x = - 4